2002
DOI: 10.4161/cbt.1.5.174
|View full text |Cite
|
Sign up to set email alerts
|

Didox (A Novel Ribonucleotide Reductase Inhibitor) Overcomes bcl-2 Mediated Radiation Resistance in Prostate Cancer Cell Line PC-3

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n .[Cancer Biology & ABSTRACTIn this study, we investigated the influence of bcl-2 overexpression on the radiosensitizing potential of Didox (DX; 3,4-Dihydroxybenzohydroxamic acid), a novel ribonucleotide reductase inhibitor, in p53-null prostate cancer cell line PC-3. The PC-3 cells were transfected with vector alone or ectopically overexpressed with CMV-bcl-2 construct. The effect of radiation (IR) or DX alone and in combination (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…Gemcitabine-resistant clones displaying RRM2 overexpression have also been reported to demonstrate altered NF-kB-binding activities (Zhou et al, 2001). Furthermore, inhibition of ribonucleotide reductase by the novel inhibitor Didox, and by hydroxyurea, have both been shown to suppress NFkB activity (Calzado et al, 2000;Inayat et al, 2002). Consistent with these observations, we observed suppression of NF-kB activity following RRM2 siRNA treatment alone.…”
Section: Discussionsupporting
confidence: 80%
“…Gemcitabine-resistant clones displaying RRM2 overexpression have also been reported to demonstrate altered NF-kB-binding activities (Zhou et al, 2001). Furthermore, inhibition of ribonucleotide reductase by the novel inhibitor Didox, and by hydroxyurea, have both been shown to suppress NFkB activity (Calzado et al, 2000;Inayat et al, 2002). Consistent with these observations, we observed suppression of NF-kB activity following RRM2 siRNA treatment alone.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our study, the NF-kB pathway was reported to be increased by RRM2 and inhibited by didox, strengthening the findings that RRM2 is a key regulator of the NF-kB pathway (40,41). Although didox exerts its activity by destabilizing ribonucleotide reductase through its free radical scavenging and iron chelating properties, didox has also been shown to have strongly inhibit NF-kB activation (42).…”
Section: Discussionsupporting
confidence: 77%
“…To date, no serious side effects have been reported with didox treatment even when administered for long periods (21). Didox has been shown to inhibit proliferation of several cancer cell types (18)(19)(20)45) and modulate other cancer chemotherapeutic agents resulting in elevated apoptosis (42). Didox was also shown to synergize with temozolomide in brain tumors and with doxorubicin in liver cancer cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…As P529 is a novel Akt inhibitor (Xue et al, 2008) whose antitumour efficacy has been proven in vivo, we hypothesised that this drug could enhance the efficacy of RT in prostate cancer. The PC-3 cell line was used because of its aggressiveness and relative resistance to RT (Inayat et al, 2002). We have found that P529 reduces dramatically the levels of phospho-Akt induced by radiation exposure (and, in a lesser extent, total Akt), which confirms that Akt is a main target of P529 in cancer cells.…”
Section: Discussionmentioning
confidence: 57%